2008
DOI: 10.1371/journal.pone.0002132
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Drug Quality in the Most Severely Malarious Parts of Africa – A Six Country Study

Abstract: A range of antimalarial drugs were procured from private pharmacies in urban and peri-urban areas in the major cities of six African countries, situated in the part of that continent and the world that is most highly endemic for malaria. Semi-quantitative thin-layer chromatography (TLC) and dissolution testing were used to measure active pharmaceutical ingredient content against internationally acceptable standards. 35% of all samples tested failed either or both tests, and were substandard. Further, 33% of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 11 publications
3
118
1
2
Order By: Relevance
“…[15][16][17] A study of artesunate content in tablets sampled from pharmacies in Kumasi, Ghana, in 2008, showed varied contents ranging from 47.9% to 99.9% with only 17.6% passing for content of active ingredients by the European Pharmacopoeia standards. 18 In this study, 20 of 24 (83.3%) samples from the market passed the assay for content; they contained the active ingredients indicated by the manufacturers and in the requisite amounts as indicated by the USP.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] A study of artesunate content in tablets sampled from pharmacies in Kumasi, Ghana, in 2008, showed varied contents ranging from 47.9% to 99.9% with only 17.6% passing for content of active ingredients by the European Pharmacopoeia standards. 18 In this study, 20 of 24 (83.3%) samples from the market passed the assay for content; they contained the active ingredients indicated by the manufacturers and in the requisite amounts as indicated by the USP.…”
Section: Resultsmentioning
confidence: 99%
“…Some Indian companies initially failed to satisfy the inspectors, and some have improved and now have products registered. Problems do persist, as Bate et al (2008) found for example for anti-malarial drugs in private urban and peri-urban retail markets in six African countries including Tanzania. There is active public scrutiny of the issue: newspapers continue to report sales of fake drugs.…”
Section: Improved Regulationmentioning
confidence: 87%
“…This statistical fi nding is also supported by the large proportion of respondents (55.2%) that mentioned lack of money as the main reason for not treating their last episodes of malaria at the rural health facility ( Table 2). Patronage of private drug vendor shops for treatment of malaria poses a great obstacle to malaria control in the country because the private vendor shops are potential sources of substandard and fake antimalarial drugs which have resulted in several treatment failures (Obinna et al 2009;World Health Organisation 2003;Bate et al 2008). Moreover, the drug vendors know little or nothing about the correct dosage of the drugs.…”
Section: Discussionmentioning
confidence: 99%